Noise source identification of split unit air conditioner system - Muhammad Hanif, Abd Rasid (2008)
Noise in split unit air conditioning system is a frequent problem for the air conditioner manufactures. Split unit air conditioners have an indoor unit and an outdoor unit connected by communication pipes. The noise can not be eliminated but it can be reduced. Noise can make in some cases limit the cooling efficiency of the air conditioner. In this project, to identify and analysis the noise at air conditioner system was investigated by using sound intensity. The investigation was carried out by varying the parameter which is the fan speed and temperature at air conditioner. For the identify where the noise source comes form the rig had been build to get the noise location and their rating by located the microphone at the rig point. The signal from the probe will be analyze by the analyzer using Pulse LabShop software from Brüel & Kjær. The results for the noise were showed in noise mapping. A different colour in the noise mapping indicates different level of noise and it showed where the most noise comes from. The highest noise sound levels occur at the front side of air conditioner which is at the fan that is about 74.784dB. The second highest noise sound level is occur at the right side which is at the compressor is about 72.115dB. Comparison of the graph will show the relation between noise and the parameter and it can be concluded that sound power level will increase as higher fan speed and the lowest temperature of the air conditioner.